Production of state institutions of rural development: the case of PSA and the PROINDER (Huellas, 2020)
Based on the Programa Social Agropecuario (PSA) and the Proyecto de Desarrollo Rural para Pequeños Productores Agropecuarios (PROINDER), this article analyzes the changes that the bureaucratic units of rural development management have undergone between the 1990s and 2010. By paying attention to institutional changes, the analysis addresses the way in which two rural development policies are produced and reproduced in different political and economic contexts. It also focuses on the way in which the continuity of both actions implied modifications in the management areas after the creation of Programs, Units, Agencies and Ministries. It has been acknowledged that the changes not only have an impact on the production of new institutions but also on the content allocated to those institutions in the constitution of a socially problematized issue that justifies a state policy.
Keywords: Rural development; state policies; institutions; governmentality